Yugoslavian Inferno: Ethnoreligious Warfare in the Balkans - Mojzes, Paul (History and politics of the 20th century, 2016)
After the fall of communism in Eastern Europe, no-one was prepared for the violent dissolution of Yugoslavia. Suddenly old terms like chetnik and ustasha found new currency, and a new term surfaced – 'ethnic cleansing' – with its sickening echo of 'final solution'. The upsurge of nationalist sentiment in Eastern Europe raises the question whether the wars in the former Yugoslavia are harbingers of things to come. Will the racist idea of the ethnically pure state crush the humanist ideal of the multicultural society? Yugoslavian Inferno provides a rich analysis of the complex issues that brought about the demise of Yugoslavia and the ensuing fratricidal warfare. It pays particular attention to the role of religion in fanning the flames of interethnic hatred and is written by a scholar uniquely placed to write it. A Yugoslavian-American with roots in both Croatia and Serbia, whose religious tradition is Protestant, rather than Catholic, Orthodox, or Muslim, Paul Mojzes is an internationally recognized authority on religion in Eastern Europe. Based on travels in the region, interviews with politicians, scholars, and religious leaders, as well as news accounts and monographs in generally inaccessible languages, and formulated after a lifetime of scholarly achievement, Yugoslavian Inferno presents insights that only a native can provide and the critical objectivity that only an outsider can offer.